How STRANGE are your study animals? - Webster, Michael M.; Rutz, Christian (Nature (London), 2020)
A new framework for animal-behaviour research will help to avoid sampling bias — ten years on from the call to widen the pool of human participants in psychology studies beyond the WEIRD. A new framework for animal-behaviour research will help to avoid sampling bias — ten years on from the call to widen the pool of human participants in psychology studies beyond the WEIRD.